Theatre Education after World War II: A Memoir - Meiklejohn, J.M.C. (Theatre Research in Canada / Recherches théâtrales au Canada, 1991)
Michael Meiklejohn (1906-1989) was one of Canada’s most influential leaders in community theatre after World War II. As full-time theatre consultant with the Department of National Health and Welfare from 1948 to 1955, he adjudicated drama festivals, gave speeches, taught workshops, published training materials, and consulted informally with other leaders in theatre education in Canada and abroad. In this memoir, written about 1981 and found among his private papers after his death, Mr Meiklejohn records his impressions of community theatre and theatre education in the burgeoning climate of post-war Canada. Michael Meiklejohn (1906-1989) fut l’un des animateurs les plus importants du théâtre local au Canada de l’après-guerre. Conseiller auprès du Ministère de la Santé et du Bien-être social de 1948 à 1955, il siégeait souvent comme juge aux festivals dramatiques, donnait des conférences et animait des ateliers sur le théâtre, faisait publier des documents sur la formation théâtrale, et maintenait des rapports informels avec tous ceux chargés de cette formation au Canada et à l’étranger. Dans ce mémoir, rédigé vers 1981 et retrouvé parmi ses papiers après sa mort, M. Meiklejohn nous offre ses impressions de l’activité théâtrale régionale et locale, et de l’éducation théâtrale dans le nouveau climat culturel du Canada d’après-guerre.